ANALISIS WACANA FEMINISME DALAM TEKS BERITA TABLOID NOVA - Anggraini, Nabila Syifa (Hasta Wiyata, 2022)
The news text about feminism in the tabloid nova can be used as a critical discourse analysis. This study aims to determine the position of women's news coverage and women's representation in tabloid Nova news texts. This study uses a qualitative descriptive method, with a critical discourse analysis approach. The data to be studied came from tabloid Nova, namely documents in the form of news texts on the August 2020 edition of the tabloid Nova. The data collection techniques in this study were carried out by reading and note-taking techniques. The data analysis technique in this study uses the Miles and Huberman model. The results of the analysis show that the discourse on feminism in the women's nova tabloid occupies two positions at once, namely as an object (which is told) and also a subject (storyteller) and the presence of women's representation in it.keywords:Â Discourse, Women, Tabloids